The birth of an opera fifteen masterpieces from Poppea to Wozzeck - Rose, Michael 1934- (Norton, 2013)
Describes the stories behind the writing and creation of fifteen different operas, detailing the circumstances of each composer's life and times and the impact their environment had on their art
L'incoronazione di Poppea -- Alceste -- Idomeneo -- Le nozze di Figaro -- Fidelio -- Barbiere di Siviglia -- Les Troyens -- Tristan und Isolde -- Carmen -- Eugene Onegin -- Otello -- Pelléas et Mélisande -- Ariadne auf Naxos -- Turandot -- Wozzeck
Keywords: Operas -- Analysis, appreciation; Oper; Aufsatzsammlung